2019
DOI: 10.1186/s13068-019-1525-5
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of LACCASE8 and LACCASE5 genes in Brachypodium distachyon leads to severe decrease in lignin content and high increase in saccharification yield without impacting plant integrity

Abstract: Background Dedicated lignocellulosic feedstock from grass crops for biofuel production is extensively increasing. However, the access to fermentable cell wall sugars by carbohydrate degrading enzymes is impeded by lignins. These complex polymers are made from reactive oxidized monolignols in the cell wall. Little is known about the laccase-mediated oxidation of monolignols in grasses, and inactivation of the monolignol polymerization mechanism might be a strategy to increase the yield of fermentab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
(58 reference statements)
2
21
0
Order By: Relevance
“…Laccases are a large group of multicopper oxidases that are widely distributed in bacterial, fungi, animals, and plants. Recent advances in high-throughput sequencing technology and molecular biology have allowed several laccases that participate in lignin polymerization to be characterized in multiple plant species (Cheng et al, 2019;He et al, 2019;Le Bris et al, 2019;Wang et al, 2019;Simões et al, 2020).…”
Section: Chlac8 Expression Parallels C-lignin Accumulation In the Clementioning
confidence: 99%
See 1 more Smart Citation
“…Laccases are a large group of multicopper oxidases that are widely distributed in bacterial, fungi, animals, and plants. Recent advances in high-throughput sequencing technology and molecular biology have allowed several laccases that participate in lignin polymerization to be characterized in multiple plant species (Cheng et al, 2019;He et al, 2019;Le Bris et al, 2019;Wang et al, 2019;Simões et al, 2020).…”
Section: Chlac8 Expression Parallels C-lignin Accumulation In the Clementioning
confidence: 99%
“…Like peroxidases, the essential functions of laccases in lignification have been revealed by loss of function approaches, using Arabidopsis, poplar (Populus trichocarpa) and Brachypodium distachyon plants (Berthet et al, 2011;Wang et al, 2015b; Le Bris et al, 2019). The laccase triple mutant (lac4 lac11 lac17) of Arabidopsis showed severe growth defects and lack of lignin in vascular tissues and fibers, but its Casparian strip structure was not affected, suggesting that laccases are essential for lignin polymerization and have non-redundant roles with peroxidases in lignification in vascular tissues (Zhao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…S1). Multiple sequence alignment revealed that PtoLAC14 shared high identity with characterized laccase proteins, including AtLAC4 and AtLAC17 from Arabidopsis [24], PtLAC2 and PtLAC3 from poplar [25,26], BdLAC5 from Brachypodium distachyon [32,33], and SofLAC from sugarcane [34] (Additional file 1: Fig. S1, Table S2).…”
Section: Identification Of the Df1 Genementioning
confidence: 99%
“…Once oxidised, the monolignols radically polymerise into the branched lignin polymer with multiple bond types resulting from the various positions of the oxygen radical on the monolignol subunit. There are 17 laccases in A. thaliana and 29 in B. distachyon (Berthet et al, 2011;Le Bris et al, 2019). Brachypodium distachyon LACCASE 5 and 8 were identified as orthologues of AtLAC17 and were shown to be responsible for lignification in interfascicular fibres (Wang et al, 2015;Le Bris et al, 2019).…”
Section: New Phytologistmentioning
confidence: 99%
“…There are 17 laccases in A. thaliana and 29 in B. distachyon (Berthet et al, 2011;Le Bris et al, 2019). Brachypodium distachyon LACCASE 5 and 8 were identified as orthologues of AtLAC17 and were shown to be responsible for lignification in interfascicular fibres (Wang et al, 2015;Le Bris et al, 2019). A laccase gene from sugarcane (SofLAC) also genetically complemented an A. thaliana lac17 mutant (Cesarino et al, 2013).…”
Section: New Phytologistmentioning
confidence: 99%